Reflection coefficient variation based on the configuration of integrated antenna and reflecting surface at 3.5 GHz - Mohd Hamzah, Siti Zainab; Abdul Malek, Norun Farihah; Ahamad, Firdaus Taqiyuddin; Mohamad, Sarah Yasmin; Jamaluddin, Mohd Haizal (IEEE, 2023)
This work offers a low profile, and enhanced microstrip patch antenna for 5G and Wi-Max applications. The proposed design is based on a patch antenna embedded with reflective surface metamaterial consisting of an array of 5 × 5 elements. The simulated and measured of S11 has been observed to determine its performance. The advancement of Frequency Selective Surface (FSS) evolution known as Reflective Surface (RS) metamaterial has been adopted to integrate with the patch antenna. This design has a small size of 107 mm × 107 mm. Furthermore, it has been integrated with the microstrip patch antenna under two different configurations which provides a variation performance antenna in terms of reflection coefficient for both configuration 1 and configuration 2, at the operating frequency of 3.5 GHz. For configuration 1, no significant changes have been observed. While in configuration 2, the resonant frequency of the patch antenna has been shifted up and down with the best S11 is -40dB at 3.4 GHz.